A new species of the genus Ptilostenius Kozlov et Le, 1988 (Hymenoptera: Scelionidae, Teleasinae) from Vietnam - Hue, Le Xuan (Academia Journal of Biology, 2015)
The genus Ptilostenius of the subfamily Teleasinae was establashed by Kozlov et Le in 1988 with only one species P. anthedon Kozlov et Le, 1988 (Kozlov M. A., Le Xuan Hue, 1988; Le Xuan Hue, 2000) from Ayunpa (Gialai province). In May 2002, from Yenthuy district (Hoabinh province), one new specimen of Ptilostenius has been collected, that differed from P. anthedon Kozlov et Le, 1988 in morphological characteristics and was described as a new species for science. Ptilostenius anthedoron Le sp. nov. Female: Head wider than long. Vertex without transverse keel. Wide temple, it’s width as 1/3 as width of eyes. Frons without depression, without transverse striae. Distance from lateral occellus to eyes longer than distance between anterior and lateral occelli. Eyes in oval form, length to width 8: 6; length of eyes about 3 times longer than length of cheek. Face of Heade almost smooth and shining. Eyes without hairs. Antenna 12 segments, with club. Scape 3, 6 times as long as wide; length of this segment in 3 times longer than length of radicle. Second segment as long as third segment; third segment as long as fourth. Club 6 segments, it’s length longer than length of scape. Length of thorax longer than width. Mesonotum without parasidal furrows. Mesonotum and scutellum with separate punctations, almost shining black. Fore and hind wings narrow. Hind wing with edging of long hairs; length of those hairs in 1/2 times longer than width of this wing. Length of fore wings in 4, 6 times longer than width of them; postmarginal veins of this wing absent; stigmal vein in 1/5 as long as marginal. Abdomen as wide as thorax. Length of abdomen longer than width of it and longer than length of thorax. First tergite as long as wide and as long as second tergite. Third tergite longer and wider than other abdominal tergites. Ovipositor extrorse, that longer than length of third tergite (13: 10). On first and second tergites with longitudinal striae. On 1/3 fore part of third tergite with longitudinal striae, other parts of this tergite smooth and shining. Body black (first segment of abdomen yellow), 1/3 last part of scape and other segments of antennae black; 2/3 fore part of scape, radicle of antennae, mandubulae and legs yellow. Length of body about 1 mm. Male unknow. Holotype: 1 female, Daphuc, Yenthuy (Hoabinh), grass in forest, 3 May, 2002 (Le Xuan Hue) (Holotype sets in the Institute of Ecology and Biological Resources). The new species differs from P. anthedon Kozlov et Le, 1988 by on second and third tergites of abdomen P. anthedon with longitudinal striae only on fore part, hairs of hind wing shorter than 1/2 width of this wing; length of third segment longer than fourth segment of antennae; length of club as long as scape of antennae. Length of out genital part shorter than last tergite of abdomen. Second to 6th tergites of abdomen and second to 6th segments of antennae dark brown. Length of body 0.8 mm.